Prevalence Of Shaktism In Hindu Bengali Community - Mrs. Ipsita Chakraborty; Dr. P. Ganesan (Journal for ReAttach Therapy and Developmental Diversities, 2023)
In Hinduism, Shaktism is one of the major and vital sects, which represent Motherhood. Women provides humanity in earthly form, nourish and endow it with character, charm and dignity, all the tremendous personal sacrifices that divinity assumes when it accepts role of motherhood. Motherhood is an assertion of women’s creative power as pinnacle of her glory; it is epitome of service and sacrifice, love and virtue, devotion and dedication and self-restraint and self-reliance. In Hindu iconography cosmic dynamic of male-female or masculine-feminine interdependence and equivalence is expressed in half Shakti, half Shiva deity known as Ardhanariswar. Hinduism does not harp on equality of sexes on idealistic plane but adduces argument of perfect balance and harmony in nature. They consider soul as sexless and women representing energy aspect of lord can’t be viewed in physical dimension. In Shaktism, it is believed that goddess as Shakti or energy of Vishnu and Shiva and revered in numerous Hindu temples and festivals. The way in which Shaktas perform their acts of adoration or worship is mysterious, full of rites and rituals which is filthy and obnoxious